Research on Disturbance Immunity Balance Control of Biped Robot Based on ESO-DDPG - Yu, Jianjun; Zhu, Ruihua; Gong, Daoxiong; Yu, Naigong; Zhou, Miaoqiang (Proceedings (International Conference on Informative and Cybernetics for Computational Social Systems. Online), 2023)
The current research on biped robots is mostly concentrated on ideal conditions, while in reality, the robot system is always subject to many external disturbances and internal parameter perturbations, which will lead to such defects as weak anti-interference ability, low real-time performance, low accuracy of controller trajectory tracking, weak balance control ability, and solving its standing posture balance problem is the premise to solve the robot walking stability. Combining the advanced depth deterministic strategy gradient algorithm (DDPG) and extended state observer (ESO), a control strategy for biped robot upright disturbance rejection balance is designed, which can quickly and timely adjust the pitch angle of the robot hip joint to restore the balance state. The DDPG controller adjusts the joint angle in real time through the difference between the actual zero torque point (ZMP) and the expected value to suppress the disturbance; ESO estimates and compensates the disturbance of unmodeled dynamics and internal parameter perturbation, and outputs joint angle compensation to improve control accuracy and rapidity. In order to verify the effectiveness of ESO-DDPG controller, it is applied to the interference suppression experiment of a stationary NAO robot. When the biped robot is disturbed by external disturbances and internal parameter perturbations, it can quickly restore its standing posture balance in real time.